ISLAMIC EDUCATION IN THE TIME OF THE ISLAMIC KINGDOM IN NUSANTARA - PITRIANI, PIPIT; ASLIHAH, ASLIHAH; HIDAYAT, WAHYU; WASEHUDIN, WASEHUDIN (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
This study aims to describe Islamic education during the Islamic kingdom in Nusantara. This study uses a literature review approach to explore Islamic education during the Islamic kingdom in the Nusantara. The formation of a Muslim community in a place is not a small matter, it involves a long process, that ultimately led to the birth of Islamic kingdoms such as Demak, Samudera Pasai, Pajang, Mataram, and so on. With the formation of Islamic kingdoms, it cannot be separated from the process of Islamic education in them by focusing on the growth and development of Islamic kingdoms, it cannot be separated from the role of education, the education system, and educational institutions in Islamic kingdoms in Nusantara